2021
DOI: 10.22271/oral.2021.v7.i1c.1134
|View full text |Cite
|
Sign up to set email alerts
|

Atypical odontalgia: An update

Abstract: Introduction: Atypical odontalgia (AO) is one of the most complicated challenges that a dentist can face for an adequate diagnosis and treatment plan. It can cause prolonged visits and costly overtreatments for the patient, increasing the time of resolution of the condition. Objective: To analyze the literature about AO, as well as its epidemiology, pathophysiology, predisposing factors, associated pathologies and treatment. Methodology: Information was searched in PubMed, SCOPUS and Google Scholar. Key words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results showed that the drugs used in AO management consist of antidepressants, anticonvulsants, analgesic opioids, antipsychotics, and topical analgesics [5,37]. Drugs for neuropathic pain recommended by the IASP include TCA, gabapentin, pregabalin, Selective Serotonin Norepinephrine reuptake inhibitors (SNRIs) as the first line, while patch lidocaine, patch capsaicin, and tramadol as the second line [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the drugs used in AO management consist of antidepressants, anticonvulsants, analgesic opioids, antipsychotics, and topical analgesics [5,37]. Drugs for neuropathic pain recommended by the IASP include TCA, gabapentin, pregabalin, Selective Serotonin Norepinephrine reuptake inhibitors (SNRIs) as the first line, while patch lidocaine, patch capsaicin, and tramadol as the second line [15].…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants, TCAs, such as amitriptyline and imipramine, are the most frequently used drugs with amitriptyline as the mainline agent if side effects or contraindications do not cause restrictions in their use [2,3,5,37,38]. The analgesic effect of TCA works with its primary mechanism of inhibiting the reuptake of serotonin and norepinephrine neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%